2018
DOI: 10.1007/s00384-018-3038-2
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat area, not body mass index, predicts postoperative 30-day morbidity in patients undergoing colon resection for cancer

Abstract: VFA but not BMI predicts morbidity following elective surgery for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…PMI is a simple but reliable method of prognostic evaluation similar to SOFA. Body composition has recently been reported as a risk factor or prognostic factor for postoperative complications [3,5,24,25]. In particular, skeletal muscle mass is considered important [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…PMI is a simple but reliable method of prognostic evaluation similar to SOFA. Body composition has recently been reported as a risk factor or prognostic factor for postoperative complications [3,5,24,25]. In particular, skeletal muscle mass is considered important [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of preoperative CTA-derived measurements also appears promising in the field of vascular surgery, in which a specific measurement, namely, core muscle size, correlates with postoperative mortality [ 61 ]. Nonetheless, morphological measurements of fat tissue seem to have a high impact on risk assessment for postoperative donor-site complications in general surgery [ 16 , 17 , 62 ] and in abdominally-based breast reconstruction [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest scientific knowledge suggests that the thus far mentioned complications occur due to a multitude of causes associated with various patient-specific traits [ 10 , 12 ] and objective morphology-based parameters [ 13 , 14 ]. Numerous recently-published studies have shown the potential of objective morphometric measurements in risk assessment for different types of surgery [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, visceral fat is a major factor in uencing the technical di culty during abdominal surgery. It has been shown in several studies [15][16][17] that obese patients are associated with a higher rate of complications such as wound infection, anastomotic stula, and longer hospital stay. Recently, it was reported that a high amount of visceral fat was associated with a signi cantly higher rate of overall complications and pancreatic stula development after PD 15,18 .…”
Section: Discussionmentioning
confidence: 99%